Clinical Application of Indocyanine Green Fluorescence Technology in Laparoscopic Radical Gastrectomy - Wei, Meng; Liang, Yize; Wang, Limei; Li, Zhen; Chen, Yuanyuan; Yan, Zhibo; Sun, Danping; Huang, Yadi; Zhong, Xin; Liu, Peng; Yu, Wenbin (Frontiers in Oncology, 2022)
Background This study aimed to observe the application and evaluate the feasibility and safety of indocyanine green (ICG) fluorescence technology in laparoscopic radical gastrectomy (LRG). Methods Patients who underwent LRG & D2 lymphadenectomy at Qilu Hospital of Shandong University were included between January 2018 and August 2019. According to whether endoscopic injection of ICG was performed, patients were assigned to the ICG group (n=107) and the control group (n=88). The clinicopathologic features, retrieved lymph nodes, postoperative recovery, and follow-up data were compared between the two groups. Results Baseline characteristics are comparable. The ICG group had a significantly larger number of lymph nodes retrieved (49.55 ± 12.72 vs. 44.44 ± 10.20, P<0.05), shorter total operation time (min) (198.22 ± 13.14 vs. 202.50 ± 9.91, P<0.05), shorter dissection time (min) (90.90 ± 5.34 vs. 93.74 ± 5.35, P<0.05) and less blood loss (ml) (27.51 ± 12.83 vs. 32.02 ± 17.99, P<0.05). The median follow-up time was 29.0 months (range 1.5-43.8 months), and there was no significant difference between the ICG group and the control group in 2-year OS (87.8% vs. 82.9%, P>0.05) or DFS (86.0% vs. 80.7%, P>0.05). Conclusions ICG fluorescence technology in laparoscopic radical gastrectomy has advantages in LN dissection, operation time, and intraoperative blood loss. The 2-year OS and 2-year DFS rates between the two groups were comparable. In conclusion, ICG fluorescence technology is feasible and safe.